Learning Nandong in schools as a medium to inform the Simeuluenese local wisdom: An anthropolinguistics approach - Tasnim Lubis (Studies in English Language and Education, 2019)
Learning traditional language gives both information about the character of the user and the value of local wisdom. Oral literature Nandong is one of the heritages from Simeulue, Aceh, Indonesia, which is important to be learned especially in Simeulue. It is included in one of the subjects in school namely mulok (local content). The objective of this study is to find out the appropriate learning model of Nandong on Simeulue Island. The interactive model was applied in this study. The data were collected by interviewing teachers, Nandong artist, and the leader and members of adat assembly in Simeulue Island. The pantoon/poetry were also collected as written data. Anthropolinguistics approach was used to analyze the data because they were related to language and human behavior. The result showed that through learning the oral tradition of Nandong, students were able to know about their custom (adat) and values in learning such as respect, obey, persistence, hard work, and ready for the challenge. The appropriate model for learning local content was a collaboration between a teacher and Nandong artist(s). This collaboration will raise more effort to keep the tradition and pass it to the young generation in Simeulue Island.